INOVASI LAYANAN SI ELSA CENTIL (VAKSINASI KELILING DESA MENCEGAH DAN MENGANTISIPASI LONJAKAN COVID 19) DALAM MENINGKATKAN LAYANAN KESEHATAN DI PUSKESMAS KALIDAWIR KABUPATEN TULUNGAGUNG - Inggil Wanudya Anarti; Trenda Aktiva Oktariyanda (Publika, 2022)
The appearance of ‘Si Elsa Centil’ becomes a service innovation which is provided by UPT Puskesmas (a public health center) located in Kalidawir for Tulungagung society. Basically, this innovation serves in order to make an easier service for the society in getting vaccine. Therefore, people do not need to put theirself into a long line to get the vaccine, this can reduce the spread of the Covid-19 virus. In this current situation, people are required to keep their distance, stay away from crowds and also reduce social mobility in order to reduce the spread of the Covid-19 virus. Number of dilemmas suffered by the society related to vaccine service during the current pandemic is the background of the problems in this study. This is due to the society’s refusal to be vaccinated and many people are still hesitant about the effects of the vaccine. This study aims to describe the extent to which the innovation ‘Si Elsa Centil’ can intensify the health services at UPT Puskesmas Kalidawir. This study uses a descriptive type of research with a qualitative approach. Data collection techniques consist of observation, interviews, and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data, and drawing conclusions.The theoretical focus in this study uses a theory of digital innovation strategy according to Nylen and Holmstron which consists of three dimensions, which are: 1) Product; 2) Environment; and 3) Organization. The result of this study indicate that the presence of innovation ‘Si Elsa Centil’ can improve the quality of service at UPT Puskesmas Kalidawir well enough. This can be seen from the increasing number of vaccination after implementing the innovation ‘Si Elsa Centil’ at UPT Puskesmas Kalidawir. Starting from June to August, resulted in an increasing registration of the first dose of vaccination and decreasing the Drop out of the second dose of vaccination at UPT Puskesmas Kalidawir. Keywords: Public Service, Health Service Innovation, Si Elsa Centil